Striga indica (Orobanchaceae) – A new parasitic species from Southern Western Ghats of India. Issue 4 (13th November 2013) - Jayanthi, P.; Kumar, K. M. Prabhu; Rajendran, A.; Thomas, Binu; Sabu, M.; Pradeep, A. K.
Abstract: A new species of Striga Lour., S. indica K. M. Prabhu, P. Jayanthi, A. Rajendran & M. Sabu is described from the Western Ghats of India. This species is shows similarities to S. barthlottii Eb. Fisch . et al., a recently described species from Morocco, but differs in unequal calyx lobes, equal bracteoles, short corolla tube, corolla colour and shape, fruit shape, stem colour, branching pattern, and presence of pubescence in various parts and host specificity. A detailed description with keys, illustrations, photographs, comparison chart and tables, conservation status and distributional details are provided. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)